PENYUSUNAN LAPORAN KEUANGAN KONSOLIDASI BERDASARKAN PENERAPAN PSAK NO. 15, PSAK NO. 22 DAN PSAK NO. 65 - Khaerudin, Taufiq; Aileen Okta Azalia; Nabilah Maulita; Endang Kartini Panggiarti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Consolidated financial statements are financial information that presents the financial position and results of operations of the parent company as well as one or more subsidiaries as if they were a single company. Current standard for preparing consolidated financial statements requires that they include companies under common control, unless such control is in question. Preparation of Consolidated Financial Statements is regulated in the statement of Financial Accounting Standards (PSAK) No. 15, PSAK No. 22 and PSAK No. 65. PSAK No. 15 describes the investment rules that must be accounted for using the equity method, where this method has a close relationship with the Consolidated Statements. PSAK No. 22 describes the accounting treatment of business mergers that can be in the form of an acquisition or consolidation of ownership, whether carried out through the acquisition of shares or net assets. PSAK No. 65 describes the consolidation criteria and also describes the consolidation procedures. This article describes the application of PSAK in the preparation of the Consolidated Financial Statements. The discussion in this article contains about investment accounting with equity method based on PSAK No. 15, business merger based on PSAK No. 22, and Consolidated Statements based on PSAK No. 65.